Pengaruh Job Insecurity dan Beban Kerja Terhadap Turnover Intention Pada PT. Telkom Akses Gorontalo (Fakultas Ekonomi, Universitas Ichsan Gorontalo, 2022)
This study aims to determine how much job insecurity (X1) and workload (X2) influence turnover intention (Y) at PT. Telkom Access Gorontalo. Methods of data collection using questionnaires administered to respondents. The analysis method uses path analysis. The results of the first test show that the variable influence of job insecurity (X1) and workload (X2) simultaneously has a positive and significant effect on turnover intention (Y) at PT. Telkom Access Gorontalo of 0.856 or 85.6%. The results of the second test show that job insecurity (X1) partially has a positive and significant effect on turnover intention (Y) at PT. Telkom Access Gorontalo, which is 0.343 or 34.3%. The results of the third test show that the workload variable (X2) partially has a positive and significant effect on turnover intention (Y) at PT. Telkom Access Gorontalo, which is 0.604 or 60.4%.